PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA KEUANGAN PADA RESPON INVESTOR - Prathiwi, Gayatri Sukma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p12, 2024)
Investor response is an investor's reaction to information related to the performance of a company. Investor response can basically be measured using the variable trading volume activity. This study aims to determine and obtain empirical evidence regarding the effect of Corporate Social Responsibility disclosure and financial performance on investor response. The population in this study was conducted on companies listed in LQ45 on the IDX for the 2016-2020 period. The sampling method used in this research is purposive sampling. The number of companies that meet the criteria are 12 companies with a total of 60 observations. This study uses data analysis techniques in the form of multiple linear regression analysis. The results show that the disclosure of Corporate Social Responsibility has a positive and significant effect on investor response, financial performance as measured by Return on Assets has a significant negative effect on investor response, while the Current Ratio and Debt to Equity Ratio have no effect on investor response.